Putting the Relationship between States and the ICC into Perspective: The Viability of National Courts in Driving Complementarity in Africa - Justin Ngambu Wanki; Grace Bilonda Mundela; Michelo Hansungule (Obiter, 2020)
This article discusses implementation challenges of the principle of complementarity; challenges in prosecuting sitting African Heads of state and nefarious warlords. The article highlights the disparity existing in physical security and remuneration between judges of national African courts and those of the ICC in similar jobs. While national judges are exposed to intimidation and influence from the most powerful in their jurisdictions, the ICC judges are provided with adequate protection and independence. Using the DRC and Kenya as case studies, this article asserts that where national courts intervene in prosecuting international crimes, heads of state would not be prosecuted. In most African states, the courts are spawned from the authoritarian regimes. This challenge renders the reliance on complementarity justice questionable.